2010
DOI: 10.1103/physrevc.81.064610
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of multifragmentation in asymmetric colliding nuclei

Abstract: We present a complete systematically theoretical study of multifragmentation for asymmetric colliding nuclei for heavy-ion reactions in the energy range between 50 MeV/nucleon and 600 MeV/nucleon by using soft and hard equations of state. This study is performed within an isospindependent quantum molecular dynamics model. To see the effect of mass asymmetry, simulations are carried out in the absence of Coulomb interactions. Coulomb interactions enhances the production of fragments by about 20%. We envision an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…η = 0.0 and η = 0.0 corresponds to mass symmetric and asymmetric nuclear reactions respectively. The study of these reactions (by keeping the total mass of the system same), actually conveys the structural effects where the total number of nucleons are equal with different combinations of the size of projectile and target nuclei [4]. From the literature, it has been concluded that the nuclear reaction dynamics is very much sensitive towards the structural effects.…”
Section: Introductionmentioning
confidence: 99%
“…η = 0.0 and η = 0.0 corresponds to mass symmetric and asymmetric nuclear reactions respectively. The study of these reactions (by keeping the total mass of the system same), actually conveys the structural effects where the total number of nucleons are equal with different combinations of the size of projectile and target nuclei [4]. From the literature, it has been concluded that the nuclear reaction dynamics is very much sensitive towards the structural effects.…”
Section: Introductionmentioning
confidence: 99%
“…We will trace this effect on the mass-asymmetric systems. The mass asymmetry of a reaction can be defined by the asymmetry parameter η = |(A T − A P )/(A T + A P )| [9], where A T and A P are the masses of the target and the projectile, respectively. The case η = 0 corresponds to the symmetric reactions, whereas nonzero values of η define various asymmetries of a reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Puri and collaboration, a detailed analysis is presented on the effect of mass asymmetry of colliding nuclei on the collective flow and its disappearance, nuclear stopping, elliptical flow, multifragmentation (at fixed energies), and nuclear dynamics (at the balance energy E bal ; i.e. energy at which collective flow disappears) by keeping the total mass of the system fixed and at different impact parameters [8,9]. A sizeable role of mass asymmetry has been found in all the cases.…”
Section: Introductionmentioning
confidence: 99%
“…The mass asymmetry of the reaction is varied by keeping the total mass of the system fixed. The quantum molecular dynamics (QMD) model [1][2][3][5][6][7][8][9][10][11][12] is used for the present study and is explained in section II. Section III is devoted to the results and discussion followed by summary in section IV.…”
Section: Introductionmentioning
confidence: 99%